Staple line reinforcement during laparoscopic sleeve gastrectomy: pros and cons - Abdelmageed, Samir A.; Helmy, Mena Z. (International Surgery Journal, 2019)
Background: Nowadays, laparoscopic sleeve gastrectomy (LSG) is the most common performed bariatric procedure. Staple line reinforcement (SLR) advised for reducing gastric leaks and bleeding after LSG. The aim of this study is to evaluate the efficacy of SLR in reducing the postoperative complications compared to non-SLR during LSG. Method: Sixty morbid obese patients were scheduled for LSG in this prospective randomized study at Sohag University Hospital in the period between March 2016 to February 2018. Patients were divided randomly into two groups: Group I included 30 patients underwent LSG with over sewing of the staple line with running suture using VLoc™ V 3/0 suture. Group II underwent LSG without SLR (n=30). Results: No cases with leaks or stenosis were detected in our series. The operative time was significantly longer in the SLR group compared to the non-SLR group (125 (110-160) vs 100 (90-125) minutes respectively, p<0.01). Staple line bleeding was detected postoperatively only in one case in group II (3.3%) which was treated conservatively. The length of hospital stay was longer in the non-reinforcement group but not significantly different (p=0.25). Conclusions: Staple line reinforcement during LSG has no superiority on the outcome of this operation, used by surgeons as a personal preference and as a security shield rather than for its advantages.